Workplace: a study of the emergency preparedness of the emergency response team vis-À-vis the Occupational Safety and Health Act 1994 - Azuddin, Bahari, Lt Kol (B); Hanum, Hassan; Razli, Ahmad (Universiti Malaysia Perlis, 2009)
Organized by Centre for Communication Skills and Entrepreneurship UniMAP in collaboration with The Ministry of Higher Education Malaysia, 5th - 6th December 2008 at Putra Palace Hotel, Perlis.